Effect Of Fines Content in Natural Soils on their Properties - Fayyad, Tawfeek (Latakia University Journal -Engineering Sciences Series, 2020)
Natural soils are used in many landfill works, such as road embankments or in the core of dams, and can be a foundation layer for many civil Structures. This study showed the effect of the ratio of fine materials expressed in many references by the passing rate of the sieve 200 after washing it, which may exceed 50% of the weight of the sample, on the behavior and physical and mechanical properties of these soils. And therefore on the mechanical resistances shown by these soils. The study was carried out on samples of the Clays soils found in the calcareous quarries used in the embakement of the Bradon dam. Samples from several on-site quarries were brought to the Soil Mechanics Laboratory at the Faculty of Civil Engineering at Tishreen University. many experiments were carried out (moisture, Atterberg Limits, Proctor, Sieve analysis, precipitation, direct shear, permeability and Oedometer). The results of the experiments were then evducted and the effect of the percentage of fins in the soils was assessed on their physical and mechanical properties. Increasing the content of fine materials in the soils, leads to increased cohesion value, the value of the Atterberg Limits and the sivelling pressure. While the value of the internal friction angle and the coefficient of elasticity modulus and the maximum dry density decreases. تستخدم الترب الطبيعية في كثير من أعمال الردم كالردم الطرقي أو في ردميات نواة السدود التربية، كما يمكن أن تكون طبقة تأسيس لكثير من المنشآت المدنية. تناولت هذه الدراسة تأثير نسبة المواد الناعمة و المعبر عنها في كثير من المراجع بنسبة المار من المنخل 200 بعد غسلها عليه و التي قد تزيد عن 50% من وزن العينة، على السلوك و الخصائص الفيزيائية و الميكانيكية لهذه الترب. و بالتالي على المقاومة الميكانيكية التي تبديها هذه الترب. أجريت الدراسة على عينات من الترب الغضارية الموجودة في مقالع الغضار المستخدم في الردميات الغضارية لسد برادون. وتم بعد ذلك تقييم نتائج التجارب و دراسة أثر نسبة النواعم الموجود في الترب على خصائصها الفيزيائية و الميكانيكية. أظهر البحث أن زيادة محتوى المواد الناعمة في الترب الغضارية الطبيعية، يؤدي لزيادة قيمة التماسك و قيمة حدود أتربرغ وضغط الانتفاخ. في حين تتناقص قيمة زاوية الاحتكاك الداخلي و معامل المرونة و الكثافة الجافة العظمى.